(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article investigates the pedagogical conditions necessary for effective organisation of independent learning activities for students at academic lyceums under the Ministry of Internal Affairs. It highlights the importance of didactic strategies, motivational frameworks and digital technologies in fostering students’ autonomy, self-regulation, and critical thinking skills within the structured environment of academic lyceums. This study presents a systematic classification of the main pedagogical conditions that contribute to the development of independent learning skills and suggests their practical application in the educational process with the aim of improving learning outcomes.